Virtue Perspectivism, Normativity, and the Unity of Knowledge - Gómez Alonso, Modesto (Daimon Revista Internacional de Filosofia, 2018)
It will be argued that personal agency, far from lacking epistemic value, contributes to knowledge in a substantial way. To this end, it will be claimed that what Sosa calls an epistemic perspective is necessary to solve the binding problem in epistemology at the three junctures at which it can occur: as the Pyrrhonian question of whether one can rationally endorse one’s epistemic rationality; as the problem of the epistemic status of guessing; and as the enquiry into the contribution of the agential perspective for evading coincidental luck. Our aim has been that of elucidating and expanding Sosa’s virtue perspectivism.